Active material and preparation method thereof
By using a mixture of high-density metal and high exothermic enthalpy metal and using thermal hydrogen treatment technology to penetrate hydrogen into the fragments, the problems of low density and component segregation of existing active fragment materials are solved, and the active fragments with high density and high energy release are achieved, which improves its destructive effect.
Patent Information
- Application Number
- CN202510341256.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The low density of existing active fragment materials and component segregation lead to poor damage effect during high-speed impact.
A mixture of high-density metal and high exothermic enthalpy metal is used as raw materials, and hydrogen elements are penetrated into the fragments through thermal hydrogen treatment technology to form active fragments with high density and high energy release.
It improves the density and mechanical properties of the fragments, enhances its damage ability and chemical energy release ability during high-speed impact, and improves the damage effect of weapons and ammunition.
Smart Images

Figure CN119859083A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energetic materials, and in particular to an active material and a preparation method thereof. Background Art
[0002] High-efficiency damage is the main goal of modern weapons and ammunition. Traditional inert metal fragments can only damage targets by penetrating and penetrating with pure kinetic energy. Although traditional energetic materials such as explosives, gunpowder and propellants have the advantages of chemical energy and explosion damage, they lack sufficient strength and can only achieve kinetic damage through chemical energy release and conversion. The significant technical feature of active fragments is that they combine the advantages of both strength and energy. They have both the mechanical strength of traditional inert metal fragments and the explosive energy similar to traditional energetic materials, which can greatly improve the damage effect of weapons and ammunition.
[0003] According to the characteristics of active fragments, the design of active fragments using high exothermic enthalpy metals has gradually attracted attention. Patent CN113651659B invented an aluminum-nickel fragment that uses a powder mixing-molding-sintering path to synthesize fragments. Although the heat release is high, the density is low; Patent CN115615260B invented a high-density, high-exothermic enthalpy refractory high-entropy alloy fragment material, including W, Al, Ti, Zr, Nb and Ta elements, which is smelted by non-consumable arc melting method. The alloy ingot of each component is repeatedly melted at least 5 times to ensure the uniformity of the chemical composition. It is easy to cause component segregation and the process is complicated.
[0004] In view of the low density and component segregation characteristics of the above-mentioned fragments, the present invention is proposed. Summary of the invention
[0005] Based on this, the present invention has the following technical solutions: In a first aspect, the present invention provides a method for preparing an active material, comprising: S1: mixing a first metal powder and a second metal powder to obtain a mixed metal powder; S2: pressing the mixed metal powder, and then performing vacuum sintering to obtain a metal alloy material; S3: subjecting the metal alloy material to thermal hydrogen treatment to obtain the active material; The first metal powder is a mixture of titanium-containing powder and pure tantalum powder, or a mixture of titanium-containing powder and pure zirconium powder; the titanium-containing powder is pure titanium powder and / or titanium alloy powder; The density of the second metal powder is 15-19.5 g / cm³.
[0006] In the present invention, the density of the second metal powder can specifically be any value among 15g / cm³, 16g / cm³, 17g / cm³, 18g / cm³, 19.5g / cm³, or a numerical range with any two of the above values as endpoints.
[0007] The present invention adopts a mixture of high-density metal and high-exothermic enthalpy metal as raw material, and combines the thermal hydrogen treatment technology to infiltrate hydrogen elements into the fragments, so as to obtain a high-density and high-energy-release active fragment; the main component of the active fragment reacts with the air to release heat during high-speed impact, and the hydrogen in the fragment is also released and reacts with oxygen, thereby improving the penetration and damage capability, and is expected to be used as a fragment material.
[0008] Preferably, the second metal powder comprises pure tungsten powder.
[0009] Preferably, the titanium alloy powder includes TA15 powder and / or TC4 powder.
[0010] Preferably, the mass ratio of the first metal powder to the second metal powder is (4-99):1.
[0011] More preferably, the mass ratio of the first metal powder to the second metal powder is (4-20):1.
[0012] In the present invention, the mass ratio of the first metal powder to the second metal powder can be any ratio of 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, and 20:1, or a ratio range with any two of the above ratios as endpoints.
[0013] Preferably, the first metal powder is composed of titanium-containing powder and pure tantalum powder in a mass ratio of 1:(1.8-8.9); more preferably, the first metal powder is composed of pure titanium powder and pure tantalum powder in a mass ratio of 1:(2-8).
[0014] Preferably, the particle size of the first metal powder is 10-80 μm, and the particle size of the second metal powder is 3-20 μm. More preferably, the particle size of the first metal powder is 10-60 μm, and the particle size of the second metal powder is 5-15 μm.
[0015] Preferably, S3 includes subjecting the metal alloy material to a thermal hydrogen treatment in a hydrogen atmosphere at 500-800° C.; preferably, the material is kept at 550-700° C. for 90-120 min.
[0016] Preferably, in S3, the flow rate of hydrogen is 0.5-3 L / min; more preferably, the flow rate of hydrogen is 0.5-2 L / min.
[0017] Preferably, in S2, the conditions of the vacuum sintering treatment include: a sintering temperature of 1200°C to 1500°C; more preferably, sintering at 1200°C to 1450°C for 120min to 180min.
[0018] Preferably, the method for preparing the active material comprises any of the following methods: S1: mixing a first metal powder and a second metal powder to obtain a mixed metal powder; S2: placing the mixed metal powder in a bag and evacuating the bag, and performing hot isostatic pressing at 1200° C. to 1450° C. to obtain a metal alloy material; S3: subjecting the metal alloy material to a thermal hydrogen treatment in a hydrogen atmosphere at 500-800° C. to obtain the active material; or, S1: mixing a first metal powder and a second metal powder to obtain a mixed metal powder; S2: granulating the mixed metal powder, and then pressing the obtained mixed metal powder to obtain a compact; S3: performing vacuum sintering treatment on the compact at 1200° C. to 1450° C. to obtain a metal alloy material; S4: subjecting the metal alloy material to a thermal hydrogen treatment in a hydrogen atmosphere at 500-800° C. to obtain the active material.
[0019] In a second aspect, the present invention provides an active material, which is prepared by the active material preparation method.
[0020] The active material and preparation method provided by the present invention can achieve controllable density and mechanical properties within a certain range by designing the composition of the active material; and the active material has sufficient mechanical properties under high-speed impact conditions to ensure integrity, and can also provide sufficient additional chemical energy to improve the damage aftereffect of the fragments. The present invention uses thermal hydrogen treatment to charge the fragments with hydrogen, which can not only regulate the mechanical properties of the active fragments, but also improve the explosive damage performance of the active fragments; at the same time, the preparation method has a short process flow, high efficiency, and controllable density and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 It is a schematic diagram of the preparation process of the active material in Example 1 provided by the present invention.
[0023] Figure 2 This is the actual hydrogen-permeated fragment obtained in Example 1 provided by the present invention.
[0024] Figure 3 It is a schematic diagram of the preparation process of the active material in Example 2 provided by the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the various raw materials used in the examples and comparative examples are commercially available conventional raw materials, and the technical means used are conventional means well known to those skilled in the art.
[0027] Example 1 This embodiment provides an active material with high energy release, and the preparation method thereof comprises the following steps (see the flow chart for a schematic diagram): Figure 1 ): (1) Prepare active raw material powder by mechanical mixing. Place 4.8 kg of pure titanium powder with a particle size of 10-60 μm, 18 kg of tantalum powder with a particle size of 10-60 μm, and 1.2 kg of tungsten powder with a particle size of 3-20 μm in a mixer and mix them thoroughly for 120 min. Mix the raw material powders evenly and weigh 100 g of the raw material powder to measure its tap density.
[0028] (2) A certain amount of the raw material powder obtained in step (1) is placed in a steel ladle of a specific volume according to the tap density, and the powder loading is assisted by vibration. After the powder is loaded, the air in the ladle is evacuated and the ladle is sealed, and then the ladle is hot isostatically pressed for 140 minutes at 1350°C and 145 MPa.
[0029] (3) After hot isostatic pressing, remove the outer sheath of the blank, grind to remove wire cutting marks, and use alcohol or acetone to remove surface oil stains.
[0030] (4) The billet obtained in step (3) is placed in a tubular furnace, and the air in the furnace is evacuated with argon. After evacuation, hydrogen is introduced and the furnace temperature is raised to 600°C and kept warm for 120 minutes. The hydrogen flow rate is 1-2 L / min. After the billet is treated, it is cooled with the furnace, and the tail gas needs to be ignited.
[0031] (5) Process the blank obtained in step (4) into a specific size and shape as required. See the actual picture. Figure 2 .
[0032] Example 2 This embodiment provides an active material with high energy release. The preparation method thereof is different from that of embodiment 1 only in that in step (2), the hot isostatic pressing pressure is 170 MPa and the temperature is 1500°C.
[0033] Example 3 This embodiment provides an active material with high energy release, and the preparation method thereof comprises the following steps (see the flow chart for a schematic diagram): Figure 3 ): (1) Prepare active raw material powder by mechanical mixing. Place 4.8 kg of pure titanium powder with a size of 10-60 μm, 14.4 kg of tantalum powder with a size of 10-60 μm, and 4.8 kg of tungsten powder with a size of 3-20 μm in a mixer and mix thoroughly for 120 minutes to mix the raw material powders evenly.
[0034] (2) Granulating and sieving the raw powder obtained in step (1) to obtain a powder with better fluidity.
[0035] (3) The powder obtained in step (2) is pressed by a powder metallurgy press at a pressure of 35 MPa to obtain a compact of a specified shape.
[0036] (4) The compact obtained in step (3) is placed in a vacuum sintering furnace at 1200°C to 1500°C and sintered for 120 min to 160 min.
[0037] (5) The billet obtained in step (4) is placed in a tubular furnace, and the air in the furnace is evacuated with argon. After evacuation, hydrogen is introduced and the furnace temperature is raised to 500°C and kept at this temperature for 90 minutes. The hydrogen flow rate is 1-2 L / min. After the billet is treated, it is cooled with the furnace, and the tail gas needs to be ignited.
[0038] (6) Screening the samples obtained in step (5) to obtain qualified fragments.
[0039] Example 4 This embodiment provides an active material with high energy release, and its preparation method is different from that of Example 1 only in that the raw material powder includes: 2.4 kg of pure titanium powder with a particle size of 10-60 μm, 14.4 kg of tantalum powder with a particle size of 10-60 μm, and 7.2 kg of tungsten powder with a particle size of 3-20 μm.
[0040] Example 5 This embodiment provides an active material with high energy release. The preparation method thereof is different from that of Embodiment 1 only in that an equal amount of titanium powder is replaced with TA15 powder of the same specification, and the remaining steps are the same as those of Embodiment 1.
[0041] Example 6 This comparative example provides an active material with high energy release. The preparation method thereof is different from that of Example 1 only in that an equal amount of titanium powder is replaced with TC4 powder of the same specification, and the remaining steps are the same as those of Example 1.
[0042] Comparative Example 1 This comparative example provides an active material with high energy release. The preparation method thereof is different from that of Example 1 in that step (4) is not included and the material is directly machined into fragments of a specific shape after hot isostatic pressing.
[0043] Comparative Example 2 This comparative example provides an active material with high energy release. The preparation method thereof is different from that of Example 1 only in that an equal amount of titanium powder is replaced with zirconium powder of the same specification, and the remaining steps are the same as those of Example 1.
[0044] Test example The present invention tests the density, energy release, etc. of the fragments of the above-mentioned embodiment and comparative example. The test results are shown in Table 1.
[0045] Test methods include: Density test method of fragments: According to "GB / T 3850-2015 Density test method for dense sintered metal materials and cemented carbide", the density of the fragments was tested 5 times and the average value was taken.
[0046] Combustion heat test method: 0.5g of active material sample is placed in an oxygen bomb, and a combustion reaction is carried out under high-pressure oxygen conditions. A calorimeter is used to measure the heat released during the reaction and the calorific value of the fragment is calculated.
[0047] Fracture strain test method: According to GB / T 7314-2017 Metallic Materials Room Temperature Compression Test Method, conduct 5 tests, record the engineering strain value of material cracking failure and take the average value.
[0048] Compressive strength test method: Conduct 5 tests in accordance with GB / T 7314-2017 Metal Material Room Temperature Compression Test Method, record the maximum engineering stress value before the material cracks and fails, and take the average value.
[0049] Hydrogen content test method: Use a balance with an accuracy of 0.0001g to measure the mass of the sample before and after hot hydrogen treatment, which are m1 and m2 respectively. The hydrogen content is 100%×(m2-m1) / m2.
[0050] Table 1
[0051] Active materials with a hydrogen content of 0.5-0.6% can increase their energy release by about 5.5% compared to hydrogen-free materials. At the same time, the introduction of hydrogen can also optimize the mechanical properties of the material. This increase in energy release and improvement in mechanical properties together enhance the damage aftereffect of active fragments.
[0052] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an active material, characterized in that: include: S1: mixing a first metal powder and a second metal powder to obtain a mixed metal powder; S2: pressing the mixed metal powder, and then performing vacuum sintering to obtain a metal alloy material; S3: subjecting the metal alloy material to thermal hydrogen treatment to obtain the active material; The first metal powder is a mixture of titanium-containing powder and pure tantalum powder, or a mixture of titanium-containing powder and pure zirconium powder; the titanium-containing powder is pure titanium powder and / or titanium alloy powder; The density of the second metal powder is 15-19.5 g / cm³.
2. The method for preparing the active material according to claim 1, characterized in that: The second metal powder includes pure tungsten powder; and / or the titanium alloy powder includes TA15 powder and / or TC4 powder.
3. The method for preparing the active material according to claim 1 or 2, characterized in that: The mass ratio of the first metal powder to the second metal powder is (4-99):
1.
4. The method for preparing the active material according to claim 1 or 2, characterized in that: The first metal powder is composed of titanium-containing powder and pure tantalum powder in a mass ratio of 1: (1.8-8.9).
5. The method for preparing the active material according to claim 1 or 2, characterized in that: The particle size of the first metal powder is 10-80 μm; the particle size of the second metal powder is 3-20 μm.
6. The method for preparing the active material according to claim 1 or 2, characterized in that: S3 includes subjecting the metal alloy material to a thermal hydrogen treatment in a hydrogen atmosphere at 500-800°C.
7. The method for preparing the active material according to claim 6, characterized in that: In S3, the flow rate of hydrogen is 0.5~3L / min.
8. The method for preparing the active material according to claim 1 or 2, characterized in that: In S2, the vacuum sintering treatment conditions include: sintering at 1200° C. to 1500° C. for 120 min to 180 min.
9. The method for preparing the active material according to claim 1 or 2, characterized in that: The preparation method of the active material includes any one of the following: S1: mixing a first metal powder and a second metal powder to obtain a mixed metal powder; S2: placing the mixed metal powder in a bag and evacuating the bag, and performing hot isostatic pressing at 1200° C. to 1450° C. to obtain a metal alloy material; S3: subjecting the metal alloy material to a thermal hydrogen treatment in a hydrogen atmosphere at 500-800° C. to obtain the active material; or, S1: mixing a first metal powder and a second metal powder to obtain a mixed metal powder; S2: granulating the mixed metal powder, and then pressing the obtained mixed metal powder to obtain a compact; S3: performing vacuum sintering treatment on the compact at 1200° C. to 1450° C. to obtain a metal alloy material; S4: subjecting the metal alloy material to a thermal hydrogen treatment in a hydrogen atmosphere at 500-800° C. to obtain the active material.
10. An active material, characterized in that The active material is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Metal-based energetic fragments with shock reactivity and their preparation method
CN113651659B
High-density and high-energy metal fuel
CN111892466A
Preparation method of explosive-loaded 3D skeleton high-entropy alloy composite energetic fragment
CN112961016A
High-strength Ti-Zr-Ta alloy and preparation method and application thereof
CN114703393A
Active damage material with mechanical strength and deflagration performance and preparation method thereof
CN117402023A